Genome-wide association and dissociation studies in Pantoea ananatis reveal potential virulence factors affecting Allium porrum and Allium fistulosum × Allium cepa hybrid - Myers, Brendon K.; Shin, Gi Yoon; Agarwal, Gaurav; Stice, Shaun P.; Gitaitis, Ronald D.; Kvitko, Brian H.; Dutta, Bhabesh (Frontiers in Microbiology, 2023)
Pantoea ananatis is a member of a Pantoea species complex that causes center rot of bulb onions (A. cepa) and also infects other Allium crops like leeks (Allium porrum), chives (Allium schoenoprasum), bunching onion or Welsh onion (Allium fistulosum), and garlic (Allium sativum). This pathogen relies on a chromosomal phosphonate biosynthetic gene cluster (HiVir) and a plasmid-borne thiosulfinate tolerance cluster (alt) for onion pathogenicity and virulence, respectively. However, pathogenicity and virulence factors associated with other Allium species remain unknown. We used phenotype-dependent genome-wide association (GWAS) and phenotype-independent gene-pair coincidence (GPC) analyses on a panel of diverse 92 P. ananatis strains, which were inoculated on A. porrum and A. fistulosum × A. cepa under greenhouse conditions. Phenotypic assays showed that, in general, these strains were more aggressive on A. fistulosum × A. cepa as opposed to A. porrum. Of the 92 strains, only six showed highly aggressive foliar lesions on A. porrum compared to A. fistulosum × A. cepa. Conversely, nine strains showed highly aggressive foliar lesions on A. fistulosum × A. cepa compared to A. porrum. These results indicate that there are underlying genetic components in P. ananatis that may drive pathogenicity in these two Allium spp. Based on GWAS for foliar pathogenicity, 835 genes were associated with P. ananatis’ pathogenicity on A. fistulosum × A. cepa whereas 243 genes were associated with bacterial pathogenicity on A. porrum. The Hivir as well as the alt gene clusters were identified among these genes. Besides the ‘HiVir’ and the alt gene clusters that are known to contribute to pathogenicity and virulence from previous studies, genes annotated with functions related to stress responses, a potential toxin-antitoxin system, flagellar-motility, quorum sensing, and a previously described phosphonoglycan biosynthesis (pgb) cluster were identified. The GPC analysis resulted in the identification of 165 individual genes sorted into 39 significant gene-pair association components and 255 genes sorted into 50 significant gene-pair dissociation components. Within the coincident gene clusters, several genes that occurred on the GWAS outputs were associated with each other but dissociated with genes that did not appear in their respective GWAS output. To focus on candidate genes that could explain the difference in virulence between hosts, a comparative genomics analysis was performed on five P. ananatis strains that were differentially pathogenic on A. porrum or A. fistulosum × A. cepa. Here, we found a putative type III secretion system, and several other genes that occurred on both GWAS outputs of both Allium hosts. Further, we also demonstrated utilizing mutational analysis that the pepM gene in the HiVir cluster is important than the pepM gene in the pgb cluster for P. ananatis pathogenicity in A. fistulosum × A. cepa and A. porrum. Overall, our results support that P. ananatis may utilize a common set of genes or gene clusters to induce symptoms on A. fistulosum × A. cepa foliar tissue as well as A. cepa but implicates additional genes for infection on A. porrum.